From Africa to Jamaica : The Making of an Atlantic Slave Society, 17751807 - Diptee, Audra (Book collections on Project MUSE., 2010)
"Rich with historical sketches of the life and experiences of slaves in Africa, on slave ships, and in Jamaica, this volume illustrates the way enslaved Africans lived and helped to shape Jamaican society in the three decades before British abolition of the slave trade. Audra Diptee's in-depth investigations reveal unexpected insights into the demographics of those captured in Africa and legally transported on British slave ships. For example, there is a commonly held belief that slave traders had a preference for adult males. In fact, the practicalities of slave raiding meant that women, children, and large groups of the elderly were particularly vulnerable during raids and were more often captured and made available for sale in the Caribbean. From Africa to Jamaica offers a new look at the Atlantic slave trade in its final years, fleshing out the historical portrait of the African men, women, and children who were sold in Jamaica and were thus among the last of the enslaved to put their stamp on Jamaican society. There is no comparable study that takes such a comprehensive approach, looking at both the African and Jamaican sides of the trade system"--Provided by publisher